Hydraulic Fracturing Mechanism in Reservoirs with a Linear Inclusion Fissure - Wang Wenwu; Zhu Xiuxing; Ye Guigen; Han Zhongying; Xue Shifeng (Journal of Engineering and Technological Sciences, 2016)
Hydraulic fracturing technology is widely used in most oil-water wells to improve production. However, the mechanism of fracturing in a reservoir with inclusion fissures is still unclear. In this study, a theoretical model was developed to determine the stress distribution during hydraulic fracturing. The line inclusion fissure was regarded as a thin bar and the stress around the artificial fracture, which is affected by a single line inclusion, was determined using the Eshelby equivalent inclusion theory. Stress intensity factors at the tip of both the artificial fracture and the inclusion were achieved, and initiation of the fracture was predicted. Furthermore, to validate the theoretical model, re-fracturing experiments were performed on a large-scale tri-axial system. The results showed that the defects reduce the intensity of the rock, which introduces the possibility that more complex fractures emerge in the reservoir. The results also showed that the fracture direction is governed by far-field stress. The obtained conclusions are helpful to better understand the mechanism of hydraulic fracturing in reservoirs.